The Moral and the Ethical Awareness and the Trademark Infringement of the Entrepreneurs in Sports Industry - Prasertchai Suksa-ard (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Copyright is defined as an idea, discovery, creativity which is intended to be publicly available. Copyright conduces benefits and commercial reputation to the inventor, such as art and scientific discoveries, etc.This is noticeable in the number of trademark infringements that have been constantly increasing during the past three years. So far, most of researchesfocusing on the study of an interpreting of the law to find relationships with business. It is clearly noticeable that there is no research focusing on studying of the moral and the ethical awareness and the trademark infringement of the entrepreneurs in sports industry. The main objectives of the research came to fulfill the most crucial gaps of all factors contributing to trademark infringement which was an ethical conduct of all entrepreneurs in sports industry.The survey method was divided into twoparts (i) quantitative was collectedthe data from the 300 representatives ofsports product entrepreneurs, retail store entrepreneurs and a group of sports service entrepreneurs, athletes and sports personnel. The sample group was selected by using sampling size, they were estimated a proportion method.(ii) The qualitative research used a group interview;A group interview was used in the qualitative phase. The key informants were selected by the purposive sampling method from three group as follow: a group of the sports product factory entrepreneur, the retail store entrepreneur and/or sports service entrepreneur, the athletes and /or sports personnel.The key informants were selected as the representative of each group, so the key informants were6 people in total. The criteria for selecting the key informants required the following qualifications:Firstly,they must be thestakeholders in the sports industry from three groups which were as follows; (1) the sports product entrepreneurs, (2) the retail store and/or sports service entrepreneur, and (3) the athletes and sports personnel participating in sports business/activities for at least three years.Secondly, a minimum of bachelor degree graduated was required.